Recruitment and coercion in Japan’s far north: evidence from colonial Karafuto’s forestry and construction industries, 1910-37 - Ivings, Steven (Labor history, 2016)
In 1905, Karafuto (Southern Sakhalin) became Japan’s second formal colony and the most sparsely populated territory in the Japanese empire. Despite its peripheral location and small population the colony was of important economic value, boasting considerable natural resources such as marine products, coal, oil and timber. This combination of richness and remoteness meant that enterprises in the colony faced an acute labour shortage. This paper examines the ways that enterprises operating in Karafuto sought to circumvent this problem by analysing the recruitment, management and maintenance of labour in Karafuto’s forestry and construction industries. It is found that a degree of coercion emerged at worksites in the colony, as management struggled to hold onto its workforce for the entirety of a project; however, coercion was not the norm and was strongly associated with specific recruitment grounds. Utilizing contemporary social research, colonial newspaper reports, oral testimony and other sources this paper finds that recruits from further afield were more likely to be involved in incidents of abuse than those in close proximity to Karafuto. Local connections, strength in numbers and mutual dependence of workers from these areas and Karafuto-based recruiters for work/labour served to reduce levels of conflict between the two parties.